Between disenchantment and re-enchantment - Platovnjak, Ivan (Poligrafi, 2025)
This article examines the speculative potential of designing a spiritually attuned artificial intelligence platform capable of supporting processes of meaning-making, fostering conditions conducive to emotional resonance, and assisting in the dis-covery of intrinsic values across diverse spiritual orientations. Situated within the socio-cultural context of late modernity—marked by the rationalization of life-worlds, increased individualization, and the erosion of traditional frameworks of meaning—we interpret the renewed emphasis on spirituality, emotional and em-bodied experience, as well as interiority, as indicative of a broader re-engagement with right-hemisphere cognitive modes, as theorized by iain McGilchrist. Rather than conceptualizing ai as a surrogate for spiritual experience or communal be-longing, we explore whether this fundamentally left-hemisphere technological ar-tifact could paradoxically be reconfigured to facilitate holistic perception, existen-tial reflection, and prosocial engagement. acknowledging the ethical complexities and epistemological constraints of such a vision, we propose a theoretical model for a digital interface that does not prescribe, but invites; that does not instruct, but listens. We conclude by posing a critical question: Can artificial intelligence, when sensitively designed, contribute to the re-enchantment of human experi-ence—not by transmitting meaning, but by enabling deeper forms of dialogical presence?
Keywords: artificial intelligence; duhovnost; iskanje smisla; kognicija desne možganske polovice; late modernitiy; meaning-making; poznomodernost; right-hemisphere cognition; spirituality; umetna inteligena